Consumption of field-realistic doses of a widely used mito-toxic fungicide reduces thorax mass but does not negatively impact flight capacities of the honey bee (Apis mellifera). (1st April 2021) - Glass, Jordan R.; Fisher, Adrian; Fewell, Jennifer H.; DeGrandi-Hoffman, Gloria; Ozturk, Cahit; Harrison, Jon F.
Abstract: Commercial beekeepers in many locations are experiencing increased annual colony losses of honey bees (Apis mellifera), but the causes, including the role of agrochemicals in colony losses, remain unclear. In this study, we investigated the effects of chronic consumption of pollen containing a widely-used fungicide (Pristine®), known to inhibit bee mitochondria in vitro, which has recently been shown to reduce honey bee worker lifespan when field-colonies are provided with pollen containing field-realistic levels of Pristine®. We fed field colonies pollen with a field-realistic concentration of Pristine® (2.3 ppm) and a concentration two orders of magnitude higher (230 ppm). To challenge flight behavior and elicit near-maximal metabolic rate, we measured flight quality and metabolic rates of bees in two lower-than-normal air densities. Chronic consumption of 230 but not 2.3 ppm Pristine® reduced maximal flight performance and metabolic rates, suggesting that the observed decrease in lifespans of workers reared on field-realistic doses of Pristine®-laced pollen is not due to inhibition of flight muscle mitochondria. However, consumption of either the 230 or 2.3 ppm dose reduced thorax mass (but not body mass), providing the first evidence of morphological effects of Pristine®, and supporting the hypothesis that Pristine® reduces forager longevity by negatively impacting digestive or nutritional processes. Graphical abstract: Image 1 Highlights: Consumption of fungicide-laced pollen produced honey bees with smaller thoraxes. Low-density gas mixes used to challenge flight behavior and increase metabolic rate. Field-realistic dose did not reduce flight performance and metabolic rates. Abstract : Chronic consumption of pollen containing the fungicide Pristine® at field-realistic concentrations by colonies of honey bees caused bees to have lighter thoraxes without affecting maximal flight performance and metabolic rate.